A study about knowledge and learning in small-scale tourism in rural and peripheral areas - Bertella, Giovanna (Universitetet i Tromsø, 2012)
The papers of this thesis are not available in Munin: 1. Bertella, G.: 'Communities of practice in tourism : working and learning together : an illustrative case study from Northern Norway', Planning & Development (2011) 8(4): 381–397. Available at http://www.tandfonline.com/doi/abs/10.1080/21568316.2011.598179 2. Bertella, G.: 'Networks of small tourism actors going online : the case of the ‘Innovative Experiences’ network' (submitted manuscript to Journal of Hospitality and Tourism Technology) 3. Bertella, G.: 'Online knowledge acquisition and sharing: an exploratory study about small tourism actors’ use of Facebook' (manuscript) 4. Bertella, G.: 'Wildlife tourism and natural sciences knowledge : challenges and critical factors' Scandinavian Journal of Hospitality and Tourism (2011) 11(1): 97–114. Available at http://dx.doi.org/10.1080/15022250.2011.540794 5. Bertella, G.: 'Knowledge in food tourism : the case of Lofoten and Maremma Toscana', Current Issues in Tourism (2010) 14(4): 355–371. Available at http://dx.doi.org/10.1080/13683500.2010.489638 6. Bertella, G.: 'A knowledge-based model for the development of food tourism' (manuscript) This study investigates small-scale tourism in rural and peripheral areas from a knowledge perspective. It aims to contribute to reflections on relevant theoretical concepts, the identification of critical factors and the development of conceptual tools for tourism development and management practice. This study is organized into four more delimited studies. The first study discusses Wenger’s theory of Communities of Practice as a possible theoretical framework for understanding the knowledge-related processes within and between small tourism operators. The second study concerns the social media and their role in knowledge acquisition and sharing by and among small tourism actors. The third and fourth studies concern wildlife and food tourism, and look into the factors critical to their development and management. This study concludes by identifying as particularly ...